The Tribolium castaneum cell line TcA: a new tool kit for cell biology - Silver, Kristopher S.; Jiang, Hongbo; Fu, Jinping; Phillips, Thomas W.; Beeman, Richard W.; Park, Yoonseong (My University, 2015)
The red flour beetle, Tribolium castaneum, is an agriculturally important insect pest that has been widely used as a model organism. Recently, an adherent cell line (BCIRL-TcA-CLG1 or TcA) was developed from late pupae of the red flour beetle. Next generation transcriptome sequencing of TcA cells demonstrated expression of a wide variety of genes associated with specialized functions in chitin metabolism, immune responses and cellular and systemic RNAi pathways. Accordingly, we evaluated the sensitivity of TcA cells to dsRNA to initiate an RNAi response. TcA cells were highly sensitive to minute amounts of dsRNA, with a minimum effective dose of 100 pg/mL resulting in significant suppression of gene expression. We have also developed a plasmid containing two TcA-specific promoters, the promoter from the 40S ribosomal protein subunit (TC006550) and a bi-directional heat shock promoter (TcHS70) from the intergenic space between heat shock proteins 68a and b. These promoters have been employed to provide high levels of either constitutive (TC006550) or inducible (TcHS70) gene expression of the reporter proteins. Our results show that the TcA cell line, with its sensitivity to RNAi and functional TcA-specific promoters, is an invaluable resource for studying basic molecular and physiological questions.
Keywords: Red flour beetle; Tribolium castaneum; TcA cell line